Migraine and Cerebellar Ataxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
A four year old boy with migraine associated with focal cerebral edema, CSF pleocytosis, and progressive cerebellar ataxia is reported from the Departments of Neurology and Radiology, Yale University School of Medicine, New Haven, CT.